Dinamika dalam Membangun Merek Kolektif pada Usaha Mikro, Kecil, dan Menengah - Dhyah Ayu Retno Widyastuti; Alexander Beny Pramudyanto; R.A. Vita Noor Prima Astuti (Universitas Muhammadiyah Yogyakarta, 2018)
The development of groups of micro, small and medium-scale enterprises (MSMEs) has been very competitive. This condition can be found in Yogyakarta Special Region (DIY), one of them is MSMEs in Krebet tourist village. The major challenge is that there have already been several location points that manufacture similar products; therefore, the crafts need to be distinguished from one another. However, it has several challenges and dynamics to manifest the plan in Krebet tourist village. Brand positioning models are relevant to be applied in this case (Keller, 2013). This article is a finding explored in the framework of the community service program. In addition to providing assistance, the authors were able to explore the dynamics of the target group. Descriptive method is used to see the reality of the methodological aspects. Data collection techniques conducted through Focus Group Discussion so that information about the conditions in Krebet Tourism Village and the dynamics of its villagers can be identified. In addition, observations were made through regular mentoring in the business group in Krebet. In order to strengthen the findings, the authors distributed questionnaires to help map some of the data needed. Furthermore, interesting points that will be presented in the article include (1) understanding of citizens about the importance of brands in business activities; (2) understanding of collective brands; (3) dynamics in building collective brands as a way to develop the potential of the tourist village.